2020
DOI: 10.7762/cnr.2020.9.4.307
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Serum Vitamin C and Uric Acid Levels, Antioxidant Status and Coronary Artery Disease: a Case-Control Study

Abstract: Coronary artery disease (CAD) is among the main causes of death in adults. Increase of oxidative stress and defects in antioxidant defense play a major role in endothelium performance and are affecting factors in the progress of atherosclerosis. The aim of this study was to measure serum levels of uric acid (UA) and vitamin C as well as the antioxidant status in patients with CAD, and compared them with those in healthy individuals. The present case-control study was performed on 44 cases and 44 controls. Demo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
3
2
Order By: Relevance
“…One reason for the lack of a significant association or increase in TAC in patients with CAD could be differences in TAC measurement methods. In a study of healthy smokers and nonsmokers, an increase in free radicals was found in smokers compared with nonsmokers 37 . However, in our study, serum TAC levels decreased in coronary artery disease, indicating the role of TAC in this disease 43 .…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…One reason for the lack of a significant association or increase in TAC in patients with CAD could be differences in TAC measurement methods. In a study of healthy smokers and nonsmokers, an increase in free radicals was found in smokers compared with nonsmokers 37 . However, in our study, serum TAC levels decreased in coronary artery disease, indicating the role of TAC in this disease 43 .…”
Section: Discussioncontrasting
confidence: 61%
“…In a study of healthy smokers and nonsmokers, an increase in free radicals was found in smokers compared with nonsmokers. 37 However, in our study, serum TAC levels decreased in coronary artery disease, indicating the role of TAC in this disease. 43 The present study results indicate that serum MDA levels are significantly increased in smokers compared with nonsmokers with CAD, so smoking may also play a role in atherosclerosis.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Coronary heart disease (CHD) is a common CVD that is one of the leading causes of morbidity and mortality worldwide. Complex interactions between multiple genetic and environmental factors are involved in its pathogenesis [ 79 ]. An important factor in the development and progression of CHD is oxidative stress, which contributes to endothelial dysfunction.…”
Section: The Application Of Se In the Prevention And Treatment Of Cvdmentioning
confidence: 99%
“…Vitamins B, D, and E showed varying degrees of reduction in the incidence of CVDs. In addition, a case–control study showed that decreased serum levels of vitamin C were significantly associated with the risk of coronary heart disease (Torkzaban, Naeini, Hassanzadeh, & Namdari, 2020). In addition, two phytosterols called lophenol (Lo) and cycloartenol (Cy) are reported in AVG, which play an important role in the regulation of blood glucose (Shakib et al, 2019).…”
Section: Phytochemistrymentioning
confidence: 99%